TEACHER TRAINING OF EARLY CHILDHOOD EDUCATION: REFLECTIONS ON THE NEED INSTRUMENTALIZATION PROFESSIONAL THEORETICAL ACTING WITH CHILDREN WITH OR WITHOUT DISABILITIES - Amorim, Gabriely Cabestre [UNESP]; Lima, Elieuza Aparecida de [UNESP]; Tiberio Araujo, Rita de Cassia [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
With the prospect that the processes of formation of teachers are social and historical constitutions, whose theme is current research focus effect in recent decades, this article seeks to identify and discuss the profile of teachers working in early childhood education in classes of children with or without disabilities. Participated in this study twenty-six teachers (specialists and regents) operating in a city in the State of Sao Paulo. For the production of data, participants responded to an interview, the results obtained show signs to ponder on the initial training and continuing teachers, the experience of the professionals interviewed and the impact of these factors on the process of teacher training for and on educational practice in groups of small children. The data demonstrated that the professionals interviewed have a background in education, and most teachers have graduate degrees, experts in special education, generalist form and/or by area of disability/disorder, teachers have training that is primarily focused on Regents pedagogy. In addition, respondents revealed that the work impossible hours continuing training; Another point to be highlighted was that teachers Regents reported difficulty in teaching children with disabilities, for not having proper training.
Keywords: Teacher Training; Child education; Special education; Deficiency